An Inverse Agonist Ligand of the PTH Receptor Partially Rescues Skeletal Defects in a Mouse Model of Jansen's Metaphyseal Chondrodysplasia. (4th December 2019) - Noda, Hiroshi; Guo, Jun; Khatri, Ashok; Dean, Thomas; Reyes, Monica; Armanini, Michael; Brooks, Daniel J; Martins, Janaina S; Schipani, Ernestina; Bouxsein, Mary L; Demay, Marie B; Potts, John T; et al.
ABSTRACT: Jansen's metaphyseal chondrodysplasia (JMC) is a rare disease of bone and mineral ion physiology that is caused by activating mutations in PTHR1. Ligand‐independent signaling by the mutant receptors in cells of bone and kidney results in abnormal skeletal growth, excessive bone turnover, and chronic hypercalcemia and hyperphosphaturia. Clinical features further include short stature, limb deformities, nephrocalcinosis, and progressive losses in kidney function. There is no effective treatment option available for JMC. In previous cell‐based assays, we found that certain N‐terminally truncated PTH and PTHrP antagonist peptides function as inverse agonists and thus can reduce the high rates of basal cAMP signaling exhibited by the mutant PTHR1s of JMC in vitro. Here we explored whether one such inverse agonist ligand, [Leu 11, dTrp 12, Trp 23, Tyr 36 ]‐PTHrP(7‐36)NH2 (IA), can be effective in vivo and thus ameliorate the skeletal abnormalities that occur in transgenic mice expressing the PTHR1‐H223R allele of JMC in osteoblastic cells via the collagen‐1α1 promoter (C1HR mice). We observed that after 2 weeks of twice‐daily injection and relative to vehicle controls, the IA analog resulted in significant improvements in key skeletal parameters that characterize the C1HR mice, because it reduced the excess trabecular bone mass, bone marrow fibrosis, and levels of bone turnover markers in blood and urine. The overall findings provide proof‐of‐concept support for the notion that inverse agonist ligands targeted to the mutant PTHR1 variants of JMC can have efficacy in vivo. Further studies of such PTHR1 ligand analogs could help open paths toward the first treatment option for this debilitating skeletal disorder. © 2019 American Society for Bone and Mineral Research.